The role of bacterial vaginosis-associated sialidase on HIV-1 infection - Traviss, Riley James (Division of Medical Biochemistry, 2023)
Studies suggest that women with Bacterial Vaginosis (BV) are at a higher risk of being infected by HIV-1. One possible reason is that bacterial vaginosis-associated bacteria (BVAB) release sialidases which alter either the virus and host cells directly or the viscosity of the female vaginal tract (FGT) mucosal barrier, increasing the likelihood of infection. This study aimed to determine the impact of bacterial sialidase on HIV-1 infection focussing specifically on the BVAB, G. vaginalis. Pseudovirus was produced by transfection of HEK293T cells and infection of TZM-bl cells was measured by luminescence. In the presence of purified commercial sialidase, pseudovirus infection increased significantly (2-fold) suggesting that sialidase enhanced HIV infection. The sialidase appeared to act on both the virus and the host cell, although the former interaction appeared to play a more important role in enhancing pseudovirus infection. Two G. vaginalis strains, 3H6 and 2HI, isolated from the FGT were cultured and tested for production of sialidase. Sialidase was purified from the culture medium of these strains by anion-exchange and gel filtration. Sialidase was successfully purified, as confirmed with a sialidase activity assay as well as SDS-PAGE. Analysis by SDS-PAGE showed two distinct bands, with approximate molecular weights of 40 – 45 kDA. Inclusion of the purified sialidase in a pseudovirus entry assay resulted in a 1.5-fold increase in HIV entry and LC/MS mass spectrometry confirmed the presence of sialidase. As not all G. vaginalis strains express sialidase, we tested whether the ATCC 14018 strain, which does not produce sialidase, could also impact HIV infection. Pseudovirus entry of TZM-bl cells was measured in the presence of the growth medium used to culture G. vaginalis. However, instead of an increase in pseudovirus infection, the culture medium inhibited virus entry. We then determined whether G. vaginalis growth altered the pH of the culture medium and/or produced an inhibitor that reduced HIV entry. When the culture medium was heated and the volume reduced, pseudovirus infection was restored albeit to a level lower than the virus only control. Increased culture medium pH did enhance infectivity but was less effective compared to heating. Overall, we concluded that BHI medium components reduced cell viability above 5ul in the absence of G. vaginalis growth and that ATCC 14018 secreted a heat labile factor that inhibited HIV infection. Therefore, it seems as though the expression of sialidase might be a very important determinant of how G. vaginalis affects HIV infection.